Enhanced performance of poly(ether sulfone) based composite proton exchange membranes with sulfonated polymer brush functionalized graphene oxide. Issue 113 (2nd November 2015) - Zhao, Yanxu; Fu, Yuqin; He, Yao; Hu, Bo; Liu, Lingdi; Lü, Jianhua; Lü, Changli
Abstract : Novel poly(ether sulfone) based composite proton exchange membranes with enhanced performance were prepared by incorporating sulfonated polymer brush functionalized GO. Abstract : Sulfonated polymer brush functionalized graphene oxide (SPB-FGO) was prepared by reversible addition fragmentation chain transfer (RAFT) polymerization, and then was introduced into a sulfonated poly(ether sulfone) (SPES) matrix to fabricate composite proton exchange membranes (PEMs). The influence of the loading content of SPB-FGO on the properties of the composite membranes was intensively studied. It was demonstrated that the properties, including proton conductivity, thermal stability, mechanical property and oxidative stability for the composite membranes, were improved as compared with those of a pristine SPES membrane. Meanwhile, the methanol permeability of the composite membranes was lower than that of the pristine membranes. The proton conductivity of SPES/SPB-FGO-2 was nearly doubled as compared with that of the pristine membrane at 25 °C. This result could be attributed to the fact that the SPB-FGO was well-distributed within the SPES membrane matrix and the ion clusters were relatively uniform in size, which made the SPB-FGO fillers create broad ionic pathways through the sulfonic acid groups in polymer brushes via interfacial interactions. Our study demonstrated that the incorporation of an appropriate amount of SPB-FGOs could improve the properties of PEMs, opening up a new design concept to fabricate organic–inorganic composite PEMs.